Hyper- and Hypo-Osmoregulatory Performance of Atlantic Salmon (Salmo salar) Smolts Infected With Pomphorhynchus tereticollis (Acanthocephala) - Finlay, Ross W.; Poole, Russell; Rogan, Ger; Dillane, Eileen; Cotter, Deirdre; Reed, Thomas E. (Frontiers in Ecology and Evolution, 2021)
Migratory species must cope with different parasite communities in different environments, but little is known about the ecophysiological effects of parasites on migratory performance. Some species/strains of acanthocephalan parasites in the genus Pomphorhynchus use anadromous salmonids as preferred definitive hosts, perforating the intestines, destroying mucosa and inducing inflammation – all of which might affect osmoregulatory function during transition between freshwater and marine environments. We used genetic barcoding to identify acanthocephalans in the intestines of wild Irish Atlantic salmon (Salmo salar L.) smolts as being the recently taxonomically-resurrected species Pomphorhynchus tereticollis. We then investigated whether natural infection intensities of this parasite were associated with reduced osmoregulatory performance, as measured by plasma chloride concentrations, or potentially elevated stress, as measured by blood glucose, of hosts in freshwater or saltwater environments (24h or 72h in 26PPT salt water, reflecting salinities of coastal waters through which smolts migrate). Although infection prevalence was high amongst sampled smolts, no associations were found within or across treatment groups between parasite abundance and plasma chloride concentrations or blood glucose levels. We found no intestinal perforations that would indicate P. tereticollis had recently vacated the intestines of smolts in either of the saltwater groups. Exploratory sampling in the two years preceding the experiment indicated that parasite prevalence and abundance are consistently high and comparable to the experimental individuals. Collectively, these results indicate that naturally-occurring abundances of P. tereticollis do not reduce osmoregulatory function or affect blood glucose content in fresh water or within 72 h of entering coastal waters, although delayed pathologies affecting marine survival may occur. Future consideration of ecophysiological interactions between anadromous fish hosts and their parasites across different osmotic environments should provide general insights into coevolution between migratory hosts and their parasites.